1994
DOI: 10.1111/j.1532-5415.1994.tb06065.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Managers and Physicians: Communication and Perceived Problems

Abstract: From the perspective of case managers, gaps in interprofessional communication may hinder the optimal care of frail elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…38,52 Even with clear policy, primary care teams are constrained by a lack of resources or limited budgets. 51,53 Unstable policy and limited resources make it difficult for health care professionals to facilitate care plans and interventions 38 and, by extension, to meet the differing expectations of patients, families, organizations, and governments. 50…”
Section: Policy and Available Resourcesmentioning
confidence: 99%
“…38,52 Even with clear policy, primary care teams are constrained by a lack of resources or limited budgets. 51,53 Unstable policy and limited resources make it difficult for health care professionals to facilitate care plans and interventions 38 and, by extension, to meet the differing expectations of patients, families, organizations, and governments. 50…”
Section: Policy and Available Resourcesmentioning
confidence: 99%
“…Th is lack of knowledge about case managers' functions and the feeling of being left out of discussions and decisions are two of the reasons for physicians' reservations about case managers. [7][8][9] Because physicians' participation before implementation was limited, their lack of knowledge is unsurprising. According to the implementation analysis, two factors contributed to physicians' absence from the discussions: their fi nancial compensation structure and very limited availability.…”
Section: Discussionmentioning
confidence: 99%
“…6 A few North American studies showed that family physicians were reluctant to introduce a new professional (ie, case manager) who could interfere in patient-doctor relationships. [7][8][9][10] Th e main objective of our study was to document the early perceptions of family physicians regarding ISD networks and case management before and after introduction and to identify obstacles to using case managers.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…2 However, home care case managers often deal with fragmentary information and lack a forum for regular review and communication with the primary care physician. 3,4 For the frail elderly population, there are conflicting results on the value of models of comprehensive follow-up in the community. In Italy, Bernabei and others 5,6 randomized seniors already receiving home care to an integrated case management system.…”
Section: Introductionmentioning
confidence: 99%